The effectiveness of a Training Program based on the Pivotal Response to reduce aggressive behavior of children with autism spectrum disorder (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Introduction: Children with autism spectrum disorder suffer from behavioral problems represented by aggressive behavior towards themselves and others, which leads to their isolation and their inability to integrate into society and the surrounding environment. Therefore, the study aimed to pre-test pare a training program based on the pivotal response in reducing the aggressive behavior of children with autism spectrum disorder. And verify its effectiveness in the pre-test  and post-test and delayed  test Methodology: The study used the semi-experimental approach by adopting quantitative design. To achieve the objectives of the study, aggressive behavior scale and training program were used. The sample of the study consisted of 30 children of autism spectrum disorder, who were randomly assigned to two control groups, and it consisted of 15 children and experiments and consisted of 15 children, The scale was applied to them, and appropriate statistical analyzes were performed. The quantitative results were extracted through the multiple variance analysis test, the accompanying analysis of variance test, and the single analysis of variance test Results: The results showed the effectiveness of the training program in reducing aggressive behavior. The results also resulted in statistically significant differences at the level of significance (a = 0.05) between the mean scores of the members of the control and experimental groups in the pre-test and post-test on the aggressive behavior scale in favor of the experimental group, and also indicated that there were no statistically significant differences at the level of significance (a = 0.05) among the average scores of the experimental group members in the post-test anddelayed test  on the aggressive behavior scale Conclusion: The study contributes to reducing the aggressive behavior, and training specialists on how to pre-test pare training and counseling programs, and early intervention programs that help these children in developing life skills.